The Impact of CAMEL Indexes on Profit Management in Banks Listed on Tehran Stock Exchange - Ebrahimi, Seyed Kazem; Bahraminasab, Ali; Seyedi, Fahimeh Sadat (International Review of Management and Marketing, 2017)
Net profit is one of the most important factors that affect the investment decisions, and has a significant effect on company's share price and management awards and reselection of them. For this reason, managers have a high incentive to increase the company's share through discretionary accruals. In a recent research conducted in the field of assessment of financial performance of banks, CAMEL indexes were presented as the most important factors affecting banks' profit management, which include five indexes of capital adequacy, asset quality, management quality, earnings quality and liquidity. Therefore, this research aims to investigate CAMEL indexes effects on banks' profit management. For this purpose, the research statistical population include banks that have been listed in Tehran Stock Exchange during the years of 2010 to 2015, which is consisted of 14 banks. For conducting this research, the multivariable regression technique and panel data were adapted. This research has one main hypothesis and 5 side hypotheses. Research hypotheses analysis results indicated that capital adequacy, management quality and earnings quality has a negative and meaningful effect on banks' profit management, and liquidity has a positive and meaningful effect on banks' profit management. Moreover, assets quality didn't have a meaningful effect on banks' profit management. Keywords: capital adequacy, asset quality, management quality, earnings quality, liquidity, banks' profit management JEL Classifications: C52, C32, Q13